Keanekaragaman Kumbang Antena Panjang (Coleoptera: Cerambycidae) pada Dua Tipe Habitat - Yulminarti Yulminarti; Dhea Nadilla (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to determine the composition and diversity of long antenna beetles. This research method is descriptive quantitative. Data collection techniques using transects and Artocarpus traps. The two types of habitat studied in this study are secondary forest and residential areas. The results showed that there were 49 individuals from 12-7 species (secondary forest-resident settlements) that belonged to one subfamily, the subfamily Lamiinae. The diversity index value obtained in the two habitat types is in the "medium" category with a value of H'= 1.86-2.22 and the evenness index value is in the "high" category with a range of E = 0.78-0.89 with a similarity value of 0.21. In conclusion, the highest beetle diversity was found in secondary forest (with a moderate category) compared to residential areas. Keywords: Diversity, Long Antenna Beetle, Lamiinae, Artocarpus Trap